Reinforcement alternatives for beams under cyclic load - A. Aboul-Nour, Louay; S. Mahmoud, Ragab; A. Khater, Mahmoud; M. Moselhy, Nesma (International Journal of Engineering and Technology, 2020)
The major cause of concrete structures deterioration is steel corrosion. Consequently, this situation has led researchers to study and test other reinforcement alternatives that are noncorrosive in nature. Rapidly emerging developments in the field of material technology has led to the development of fiber reinforced polymers (FRP). This research focuses on the flexural behavior of carbon, glass, aramid, and basalt (CFRP, GFRP, AFRP, and BFRP) fiber reinforced polymers bars as alternatives to the traditional steel reinforcement in concrete. The study involves a nonlinear numerical finite element analysis of a simply supported reinforced concrete beams subjected to cyclic loading, where the ANSYS program is utilized. The numerical model verification is executed on the experimental beams for ensuring the efficiency of ma-terial models, cyclic loading and various elements. Hysteresis curves are produced for each beam and analyzed, where loads, deflections, and cracks propagation are inspected and discussed. The results reveal that, the full replacement of traditional steel bars with CFRP bars gives the greatest increase in the ultimate load capacity by 38.5%. Also, other results are summarized in this paper.Â